2011
DOI: 10.1080/03050629.2011.622627
|View full text |Cite
|
Sign up to set email alerts
|

Microfoundations of Civil Conflict Reconciliation: Ethnicity and Context

Abstract: Comparative work on reconstruction and peace building in wartorn countries is dominated by a macro-oriented approach, focusing on structural political reforms, legal issues, disarmament, demobilization and reintegration of (rebel) soldiers, and repatriation of the displaced. This article offers a different perspective, examining micro-level determinants of reconciliation. Earlier research indicates that political attitudes in post-ethnic conflict societies are shaped by ethnic affinity. A large literature on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 60 publications
(56 reference statements)
2
25
2
Order By: Relevance
“…This finding is more in line with arguments of 'war-weariness', which propose that people closer to the battlefield are more disposed to reconciliation (e.g. Bakke et al, 2009;Dyrstad et al, 2011). In a study from South Africa, Gibson and Gouws (2001) found little effect of context on tolerance.…”
supporting
confidence: 77%
“…This finding is more in line with arguments of 'war-weariness', which propose that people closer to the battlefield are more disposed to reconciliation (e.g. Bakke et al, 2009;Dyrstad et al, 2011). In a study from South Africa, Gibson and Gouws (2001) found little effect of context on tolerance.…”
supporting
confidence: 77%
“…In societies affected by protracted conflict, individuals directly exposed to violence and losses tend to adhere more strongly to the conflict‐supporting shared beliefs of the society—also termed the “ethos of conflict” or “conflict ideology” (Canetti et al, ; Hobfoll, Canetti‐Nisim, & Johnson, ; Lavi, Canetti, Sharvit, Bar‐Tal, & Hobfoll, ). As illustrated in previous research, exposure to violence and war losses that cannot be recovered (i.e., the loss of loved ones) exert a negative impact on intergroup attitudes in wartime and postwar situations (Bakke, O'Loughlin, & Ward, ; Besser & Neria, ; Canetti‐Nisim, Halperin, Sharvit, & Hobfoll, ; Dyrstad, ; Dyrstad, Buhaug, Ringdal, Simkus, & Listhaug, ; Gould & Klor, ; Halperin, Canetti, Hobfoll, & Johnson, ; Hayes & McAllister, ; Lavi et al, ; Pham et al, ; Punamaki, Qouta, & El Sarraj, ; Samii, ). We contribute to this literature in novel ways by examining how exposure to violence and war‐related losses impact individuals' transitional justice preferences, which are closely linked to the “ethos of conflict” that tends to persist long after wars end (Bar‐Tal & Halperin, 2011; Bar‐Tal et al, ).…”
Section: Discussionmentioning
confidence: 84%
“…Among the second group, studies have contended that variables other than violence take the front seat when it comes to explaining attitudes toward peace. For example, focusing on the 2001 Macedonian civil conflict, Dyrstad et al (2011) found that ethnicity trumped all other individual and contextual factors-including exposure to violence-in explaining people's support for the Ohrid Framework Agreement, the deal that brought the conflict to an end. Exploring citizens' attitudes toward peace in the Israeli-Palestinian conflict, Newman (2012) found that present conditions-largely related to lack of trust in Arab aspirations-rather than past experiences of conflict were what really helped to understand Israeli unwillingness to make concessions for peace.…”
Section: Exposure To Violence and Attitudes Toward Peacementioning
confidence: 99%